Sociodemographic, Prenatal and Postnatal Characteristics of Children and Adolescents with Speech and Language Disorders - İfakat Şule Korkmaz; Esra Hoşoğlu; Serdar Karakullukçu; Bahadır Turan (Ahi Evran Medical Journal)
Purpose: This study aims to identify risk factors for speech and language disorders by comparing the sociodemographic, prenatal, and postnatal characteristics of children and adolescents with speech and language disorders to those of healthy individuals.